Metastatic Papillary Thyroid Carcinoma with Multifocal Synchronous Transformation to Anaplastic Thyroid Carcinoma. (28th September 2016) - Benedict, Mark; Costa, Jose
Abstract : Papillary thyroid carcinoma is a common malignancy to affect the thyroid and is typified by a nonaggressive nature and low rates of mortality. In contrast, anaplastic thyroid carcinoma is the most aggressive thyroid malignancy with a mortality rate of nearly 90% and survival typically of only six months after the diagnosis is made. The transformation of papillary thyroid carcinoma to anaplastic thyroid carcinoma is well documented in the literature but is uncommon and in most instances is reported as a case report or small series only. Transformation of papillary thyroid carcinoma to anaplastic thyroid carcinoma usually takes place in the thyroid itself or in the adjacent lymph nodes. Only on rare occasions does a transformation occur in a papillary thyroid carcinoma metastasis outside of these locations. In the present case report and subsequent discussion we highlight an unusual case of PTC with transformation to anaplastic thyroid carcinoma, which is shown to involve numerous locations to include near total lung parenchyma obliteration. We also discuss the differential diagnostic challenges when faced with a thyroid malignancy that is negative for thyroglobulin.